Reliability and validity of test concepts for the cross-country skiing sprint - Stöggl, T.; Lindinger, S.; Müller, E. (Medicine & Science in Sports & Exercise, 2005)
Abstract: Purpose: This study was conducted, first, to develop a test concept for the new cross-country (XC) skiing sprint and to check test reliability and validity, and, secondly, to test the hypothesis that short-duration maximal speed in double poling (DP) predicts DP sprint performance over race distance (1000-1500 m).